HUBUNGAN KEPATUHAN PASIEN DALAM PENGGUNAAN OBAT ANTIHIPERTENSI DENGAN HEALTH BELIEF MODEL DI POLI JANTUNG RSUD DR HARDJONO PONOROGO - Andari, Susilowati; Rakhmawati, Erna Agung; Handayani, Tatik; Hidayah, Zulfah Nurul (Jurnal Riset Kefarmasian Indonesia, 2025)
Hypertension is a condition where there is an increase in blood pressure. chronically because the heart pumps blood more strongly to meet the body's needs. The Health Belief Model is the first theory in the health sector that focuses on an individual's belief or perception of an illness. The aim of this study was to determine the relationship between compliance of hypertensive patients in using antihypertensive drugs with health belief model at the heart clinic of RSUD Dr. Hardjono Ponorogo. The method used is observational analytical instruments using questionnaires that have been tested for validity and reliability. The sample in this study was hypertensive patients at the heart clinic of RSUD Dr. Hardjono Ponorogo in April 2024 who met the inclusion criteria. The data results were analyzed using the Spearman method with SPSS. The results of the study show that the health belief model has a relationship with medication adherence in hypertensive patients. Significant value. obtained is 0.000 and the correlation coefficient (r) is 0.660. In conclusion, the health belief model and compliance behavior variables. have a unidirectional and strong relationship.